Effectiveness of digital co-creation platform in remote pulmonary rehabilitation for older adults with chronic obstructive pulmonary disease: a randomized controlled trial - Huang, Xueying; Song, Xianjing; Sun, Manyao; Hou, Yi; Nan, Jiang; Gao, Jing; Fu, Songxin; Jiang, Yuyu (Frontiers in Public Health, 2025)
AimsDespite proven benefits, older adults with chronic obstructive pulmonary disease (COPD) face significant challenging in adhering to telehealth-enabled pulmonary rehabilitation (Tele-PR). Co-creation represents an innovative approach to behavioral intervention. The aim of this study is to investigate the effect of improving activation and adherence among older adults with COPD who accepted an intervention incorporating co-creation sessions.MethodsA total of 102 older adults diagnosed with COPD were randomly assigned to the control group (PR group) or digitalization co-creation group (CC-CoI group). The intervention lasted for 12 weeks, and the follow-up was 12 weeks. The primary outcomes were patient activation and Tele-PR adherence. The secondary outcomes included dyspnea symptoms, exercise self-efficacy, self-management ability, social support, cognitive level, and satisfaction with medical service. Data were collected at baseline, week 12, and week 24.ResultsA total of 102 participants completed the study. At weeks 12 and 24, there were statistically significant differences in patient activation (p < 0.001, p < 0.001) between the two groups. Tele-PR adherence remained effectively maintained in the CC-CoI group (p = 0.607, p = 0.332), while the PR group showed a significant decline (p = 0.006, p < 0.001). The CC-CoI group also exhibited significant improvements in the modified Medical Research Council (mMRC) scale score, Exercise Self-Regulatory Efficacy Scale (Ex-SRES) score, COPD Self-Management Scale (CSMS) score, Perceived Social Support Scale (PSSS) score, and COPD knowledge.ConclusionThese results indicate that digital co-creation enhances the active participation of older adults in Tele-PR and fosters the development of virtual communities along with the onset of altruistic behaviors in individuals. This approach encourages patients to apply their knowledge for self-management of health behaviors, which in turn, enhances their adherence to rehabilitation exercise and leads to better health outcomes.Clinical trial registrationChinese Clinical Trial Registry (ChiCTR): ChiCTR1900028563/December 27, 2019. http://apps.who.int/trialsearch/default.aspx.